Transboundary freshwater dispute resolution : theory, practice, and annotated references - Beach, Heather L. (Water resources management and policy series., 2000)
"This work attempts to provide a comprehensive review of the relevant literature on managing conflicts stemming from the quantity and quality problems of water around the world."--Preface